KUALITAS INFORMASI AKUNTANSI SEBELUM DAN SESUDAH KONVERGENSI IFRS DI INDONESIA (Studi Empiris pada Perusahaan Non Keuangan di BEI Periode 2005-2012) - Hafida Istiqomah Nuraini (Master in Accounting Program, 2013)
The purpose of this study is to analyze the difference between the quality of accounting information before and after IFRS convergence in Indonesia. This study is using value relevance, earnings management, and timely loss recognition variables to examine the quality of accounting information.Data that is used in this research are all of companies that listed in IDX except banking and financial sectors at observation period before IFRS (2005-2008) and after IFRS (2009-2012). Tests of this study using multiple linear regression test and wilcoxon signed rank test.The result of this study shows that the application of International Financial Reporting Standards (IFRS) in Indonesia can raise quality of accounting information which is the increase of value relevance and the decrease of earnings management, but on the other hand, IFRS has not effect increase to timely loss recognition.